Surgical correction for adult spinal deformity increases acetabular lateral coverage of femoral heads - Qiang Luo (BMC, 2021)
Abstract Background Studies explaining the relationship between hip and spine reported that spinal corrective surgery affected acetabular orientation and changes in pelvic tilt were capable of influencing radiographic measures of acetabular coverage. This study aimed to assess the change in coronal parameters for acetabular coverage as a result of adult spinal deformity (ASD) correction and to analyze the relationship between the postoperative changes in sagittal spinopelvic parameters and coronal acetabular coverage parameters. Methods Fifty-two consecutive patients who had undergone multilevel spinal surgical correction were enrolled and evaluated. Coronal acetabular coverage parameters included Tönnis angle (TA), lateral center edge angle (LCEA), and the angle of Sharp (SA). All radiographic parameters were evaluated at the preoperative and the postoperative 1 year. Paired t test was used to determine whether there were significant changes between the time points. Bivariate correlation and linear regression analysis were used to assess the relationship between the postoperative changes of spinal alignment and acetabular orientation. Results The surgical correction resulted in significant decrease of TA, increase of LCEA and SA, respectively (p < 0.001). The changes in pelvic tilt (PT) demonstrated weak correlation on TA (β = 0.117, p < 0.001 for right; β = 0.111, p < 0.001 for left). Conclusions Although the surgical correction of ASD significantly changed PT resulting in increased acetabular lateral coverage parameters, the correlation between the changes of PT following sagittal correction of ASD and acetabular coverage parameters was low. Trial registration This study was retrospectively registered with approval by the institutional review board (IRB) of our institution (approval number: KHNMC-2020-10-010).